CRITICAL CONSIDERATIONS OF MODERN MARXISM IN THE ANALYSIS OF TRADITIONAL MARXISM IN ART WITH A CASE STUDY OF THE WORKS OF BARBARA KRUGER - Apena Esfandiari (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Traditional Marxism in art, before the advent of modern Marxism, had a reductionist and sometimes critical nature. Instead of expanding the reader's understanding of art, the Marxist critic insisted on only one form, such as realism; Whereas, from the point of view of modern Marxism, history is not as a field of work of art and something that does not have a fundamental presence in the work of art and only occasionally shows itself. By creating its social environment, art also creates its historical moments. Just as the historical moments of forms do not coincide with the historical moments of social change, so the aesthetic social environment is different from the sociological social environment, and the two should not be equated. The social environment is studied as one of the elements of artistic creation not in terms of visual value but in terms of explanatory value; That is, from the marginal aspects of sociology or history, which has a sociological orientation, in the past, we will arrive at an aesthetic interpretation that connects the social dimension as an artistic element. The main objectives of the research: to observe moderation in the view- is between the transcendental views (which respect the social dimension of art) with the requirements of the contemporary period. Realization and practical proof of this issue in the way of presenting Krueger's works as an artist committed to his society, who shares in the concerns of societies and, as a result, proves his historical role as an artist and causes the historical progress of art to get his share. The expansion of theoretical knowledge, analysis of the past situation of art history, providing more comprehensive solutions according to the social situation in the contemporary period, helping to improve educational methods are other goals. Type of research in terms of nature and method: descriptive-analytical in the theoretical branch.